Our planet earth - Lye, Keith (Kingfisher London, 1994)
Focusing on the Earth, this is part of a 12-volume encyclopaedia which aims to reflect the concerns of the National Curriculum. The book investigates the planet's physical features, its resources, and our shared responsibility for its conservation.